Analisis Yuridis Pemenuhan Unsur Tindak Pidana Penghinaan dan Ujaran Kebencian (Hate Speach) Perspektif KUHP dan UU ITE - Nuryani; Hajairin; Ilham (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to determine the elements of criminal offenses of insult and hate speech according to the Criminal Code and ITE Law, and to determine the impact of criminalization of hate speech and insult on social media. This research uses a normative method to examine justice based on the community's perspective on the modification of the purpose of punishment in the Criminal Code. The approaches used include conceptual, legislative, and comparative approaches. The legal sources used are secondary data, consisting of primary, secondary, and tertiary legal materials. Data collection is conducted through literature study by analyzing written documents and electronic sources related to the criminal act of insult and hate speech. Thus, this research aims to provide a better understanding of the law and norm system related to the criminal offense of insult and hate speech. This study concludes that the legal regulation of hate speech in Indonesia has evolved through the Criminal Code and the ITE Law, but its implementation still faces challenges such as diverse interpretations and potential abuse, thus requiring improved regulation and a comprehensive approach to increase the effectiveness of handling hate speech and protect human rights.